Training and Implementation of DIGICOM to Enhance Elementary Science Learning through Community Service Innovation - Bambang Subali; Ian Yulianti; Imam Sumpono; Nila Prasetya Ariyani; Natalia Erna Seytaningsih; Toni Wahyudi (Universitas Negeri Semarang, 2024)
This community service program was conducted to enhance the competencies of elementary school teachers in utilizing the innovative teaching aid Digital Image Creator for Optical Microscope (DIGICOM) to strengthen science learning. The program was motivated by the limited availability of digital microscopes in schools and the low ability of teachers to adapt optical learning technologies. The main objective was to train teachers from the Imam Bonjol Teacher Working Group (KKG) in Banjarnegara Regency to modify conventional optical microscopes into digital microscopes integrated with imaging systems. The training was carried out online through a series of activities including lectures, discussions, camera adapter design workshops, DIGICOM implementation, and mentoring with follow-up evaluations. A total of 51 teachers actively participated in the practice sessions and group projects. The results showed a significant improvement in teachers’ conceptual understanding, technical skills, and motivation to implement DIGICOM in science learning. More than 85% of participants were able to operate the modified tool successfully and apply it in their schools. These findings demonstrate that the implementation of DIGICOM is an effective educational innovation to improve the quality of science learning in elementary schools and strengthen teachers’ digital literacy in science education.